Young men who have sex with men's awareness, acceptability, and willingness to participate in HIV vaccine trials: Results from a nationwide online pilot study. Issue 43 (8th October 2019) - Connochie, Daniel; Tingler, Ryan C.; Bauermeister, José A.
Abstract: Background: New cases of human immunodeficiency virus (HIV) among young men who have sex with men (YMSM) underscore the need to examine their willingness to use biomedical prevention methods, including an acceptable and efficacious HIV vaccine. We examined whether YMSM's vaccine altruism and vaccine-related socials concerns factors were associated with HIV vaccine acceptability across two vaccine efficacy scenarios, and their awareness and willingness to participate in HIV vaccine research. Methods: This secondary analysis uses data from a mHealth trial with YMSM at heightened HIV risk (N = 137; 50% racial/ethnic minority; M = 21.7 years). Most YMSM (91.2%) had tested for HIV, and 17.5% (N = 24) reported a prior STI. We used paired-samples t -test to compare differences in efficacy acceptability (50% vs 85%), followed by multivariable regressions examining whether vaccine attitudes (altruism and social concerns) were associated with vaccine acceptability and awareness and willingness to participate in HIV vaccine trials. We controlled for age, education, race/ethnicity, prior HIV testing, and STI diagnosis in our analyses. Results: Acceptability for the HIV vaccine with 85% efficacy (M = 8.86; SD = 1.76) was greater than acceptability in the 50% efficacy scenario (M = 7.60; SD = 2.58). Altruistic attitudes were associated with greater vaccine acceptability at 50% (β = 0.62) and 85% (β = 0.59) efficacy. Higher educational attainment was negatively associated with a vaccine with 50% efficacy (β = −0.20, but not for 85% efficacy. Greater vaccine-related social concerns were negatively associated with HIV vaccine research awareness (AOR = 0.38 (95% CI: 0.22, 0.67). Willingness to participate in a HIV vaccine trial was positively associated with age (β = 0.18) and altruism (β = 0.60), and negatively associated with education (β = −0.21). Conclusions: YMSM find HIV vaccines as an acceptable prevention modality and are willing to participate in HIV vaccine trials. Findings highlight the need to consider YMSM's altruistic and social concerns attitudes in HIV vaccine research and explore how to leverage these attitudes in research campaigns. ClinicalTrials.gov Identifier: NCT02842060.